(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Mobile technologies have become a crucial functional element of modern organizations. They provide uninterrupted access to information, regardless of the userâ€™s geographic location and time. Customer service, quality, satisfaction and retention are key proponents of measuring success and profitability in any organization. Due to the exponential growth of information technology, banks face dual competitive pressures to provide service quality and administrative efficiency. Accordingly, banks need to retain their existing users of mobile banking (m-banking) services to be able to benefit long term from this sustained usage behavior. The problem for banks is that the current understanding of determinants of m-banking sustained usage is limited. We propose some modifications to the DeLone and McLean Model (2003) of Information Systems Success in light of descriptive and relational studies, whereby the universal model may be applicable in post adoption user retention context. Using the findings of the review of theories and models, banks in Saudi Arabia can improve their m-banking strategies to achieve higher retention rates of existing users of m-banking services. While this study focused on m-banking user retention in the Saudi Arabian context catering to post adoption scenario, the purpose of this study is also to establish a universal measurement model for post adoption user perception of m-banking services, with global applicability.Â